JARID1B expression and its function in DNA damage repair are tightly regulated by miRNAs in breast cancer. Issue 4 (18th March 2019) - Mocavini, Ivano; Pippa, Simone; Licursi, Valerio; Paci, Paola; Trisciuoglio, Daniela; Mannironi, Cecilia; Presutti, Carlo; Negri, Rodolfo
Abstract : JARID1B/KDM5B histone demethylase's mRNA is markedly overexpressed in breast cancer tissues and cell lines and the protein has been shown to have a prominent role in cancer cell proliferation and DNA repair. However, the mechanism of its post‐transcriptional regulation in cancer cells remains elusive. We performed a computational analysis of transcriptomic data from a set of 103 breast cancer patients, which, along with JARID1B upregulation, showed a strong downregulation of 2 microRNAs (miRNAs), mir‐381 and mir‐486, potentially targeting its mRNA. We showed that both miRNAs can target JARID1B 3′UTR and reduce luciferase's activity in a complementarity‐driven repression assay. Moreover, MCF7 breast cancer cells overexpressing JARID1B showed a strong protein reduction when transfected with mir‐486. This protein's decrease is accompanied by accumulation of DNA damage, enhanced radiosensitivity and increase of BRCA1 mRNA, 3 features previously correlated with JARID1B silencing. These results enlighten an important role of a miRNA's circuit in regulating JARID1B's activity and suggest new perspectives for epigenetic therapies. Abstract : We show that 2 microRNAs, strongly underexpressed in breast cancer tissues and targeting JARID1B 3′‐UTR, when transfected, modulate JARID1B expression and confer radiation sensitivity to breast cancer cells. This observation sheds light on the post‐transcriptional regulation of JARID1B and reinforces the recently established link between JARID demethylases and DNA repair in breast cancer cells.